FAMA: A Molecular Link between Stomata and Myrosin Cells. (October 2016) - Shirakawa, Makoto; Ueda, Haruko; Shimada, Tomoo; Hara-Nishimura, Ikuko
Abstract : Plants use sophisticated defense strategies against herbivores, including the myrosinase-glucosinolate system in Brassicales plants. This system sequesters myrosinase in myrosin cells, which are idioblasts in inner leaf tissues, and produces a toxic compound when cells are damaged by herbivores. Although the molecular mechanisms underlying myrosin cell development are largely unknown, recent studies have revealed that two key components, a basic helix-loop-helix (bHLH) transcription factor (FAMA) and vesicle trafficking factors (such as SYNTAXIN OF PLANTS 22), regulate the differentiation and fate determination of myrosin cells. FAMA also functions as a master regulator of guard cell (GC) differentiation. In this review, we discuss how FAMA operates two distinct genetic programs: the generation of myrosin cells in inner plant tissue and GCs in the epidermis. Trends: Myrosin cells in Arabidopsis thaliana provide a valuable model for studying idioblast development. The bHLH transcription factor FAMA is an essential component for the differentiation of ground meristem cells (stem cells in inner tissues) into myrosin cells. This finding indicates that a common regulatory pathway generates two distinct cell types in leaves: epidermal GCs and inner-tissue myrosin cells. Auxin accumulation and/or flux levels are required for the cell fate determination process that selects the myrosin lineage cells from a pool of ground meristem cells. In particular, the endocytosis-dependent polar localization of the auxin efflux carrier PIN1 has a critical role in suppressing myrosin cell development.